Does monthly self-management of vaginal ring pessaries reduce the rate of adverse events? A clinical audit. (December 2022) - Moore, Kate H.; Lammers, Karin; Allen, Wendy; Parkin, Katrina; te West, Nevine
Abstract: Objective: To determine the rate of adverse events (AE) in women who self-manage their vaginal ring pessary on a monthly basis. We hypothesised that the AE rate would be lower compared to previously published traditional management protocols. Study design: Audit study of 75 women with pelvic organ prolapse and/or stress incontinence, who were fitted with a vaginal ring pessary during a five-year period, and who have self-managed their vaginal rings for at least two years, in a tertiary referral urogynaecology clinic. Main outcome measures: AEs included vaginal bleeding, malodorous vaginal discharge, extrusion of the device, pain/discomfort, and disorders of defaecation or de novo urinary incontinence. AEs that led to discontinuation of usage were termed "major". Results: Of the 75 women who were taught to self-manage their ring pessary, 68 were initially successful. At a median follow-up of 50.5 months [IQR 43–76 months; median 4.2 years], 36 women (52.9%) were still using their ring pessary. Five women (7.4%) had vaginal erosions and bleeding leading them to cease pessary use (four proceeded to surgery). Three minor AEs were identified (4.4%), resolving after discontinuation of ring use two weeks. Thus, the overall AE rate was 11.8% (8/68). Conclusions: In contrast to previous published AE rates of 43–56% in women having ring changes at a clinic every 4–6 months, the AE rate was 12% in the women who performed monthly self-management of vaginal ring pessaries. Such information should be made available to patients considering a vaginal ring pessary.